Laparoscopic Evaluation of the Tuboperitoneal Factors in Infertility - Khan, MI; Jerin, J; Jesmin, S; Chowdhury, TA (BIRDEM Medical Journal, 2014)
Objective: The aim of the study is to describe the tuboperitoneal findings in selected infertile patients by laparoscopy. Methods and Materials: This cross-sectional study was carried out at the infertility center in BIRDEM during the period of September 2002 to February 2003. A total of 50 patients were selected for laparoscopy and dye test. Those patients who had medical disorder and contraindications for laparoscopy were excluded from the study. Patients with infertility due to male factors were also excluded from this study. Laparoscopy was scheduled in secretory phase of menstruation. Results: Among the study population, 35 (70%) patients were primary infertile group while 15 (30%) patients were secondary infertile group. According to age distribution, 20 (57%) patients of primary infertility and 8 (53%) patients of secondary infertility belonged to age group 25-30 years. Duration of infertility was between 2 yrs to 5 yrs in 45% of patient where 30% cases had been infertile for 5 yrs to 10 yrs. Laparoscopy revealed normal findings in 14 (28%) patients and ovarian cause like chocolate cyst and polycystic ovary in 21 (42%). Peritoneal pathology like adhesion or endometriosis was detected in 19 (38%) cases. Bilateral tubal occlusion was found in 4 (8%) cases and unilateral tubal occlusion in 7 (14%) cases. Conclusion: Laparoscopy is a necessary diagnostic tool for evaluation of tubo-peritoneal pathology in infertile women. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18546 Birdem Med J 2014; 4(1): 9-12